The Relationship between Sleep Quality and Academic Grades in Students of the Faculty of Medicine, Abulyatama University: Hubungan Kualitas Tidur Dengan Nilai Akademik Pada Mahasiswa Fakultas Kedokteran Universitas Abulyatama - Selian, Fitri Alfani; Atika, Ratih Ayu; Wahab, Abdul (Yayasan Sagita Akademia Maju, 2025)
This study aims to determine the relationship between sleep quality and academic grades in Abulyatama University Faculty of Medicine students. The research method used is descriptive quantitative using a cross sectional design conducted in July 2024. The study was conducted on 77 samples with total sampling technique.